To transform each linear equation into slope-intercept form (y = mx + b), we'll rearrange the equations accordingly. Here are the transformations:
-
For the equation: \(2x - 5y + 15 = 0\):
Rearranging gives: \[ -5y = -2x - 15 \] Dividing by -5: \[ y = \frac{2}{5}x + 3 \]
-
For the equation: \(15y - 2 = x\):
Rearranging gives: \[ 15y = x + 2 \] Dividing by 15: \[ y = \frac{1}{15}x + \frac{2}{15} \]
-
For the equation: \(4y - 2x = -12\):
Rearranging gives: \[ 4y = 2x - 12 \] Dividing by 4: \[ y = \frac{1}{2}x - 3 \]
-
For the equation: \(8x = 2y - 2\):
Rearranging gives: \[ 2y = 8x + 2 \] Dividing by 2: \[ y = 4x + 1 \]
Now, summarizing the equations in slope-intercept form:
- \( y = \frac{2}{5}x + 3 \)
- \( y = \frac{1}{15}x + \frac{2}{15} \)
- \( y = \frac{1}{2}x - 3 \)
- \( y = 4x + 1 \)
Now, you can match these to the original equations you've been given.